Leber's hereditary optic neuropathy (LHON/11778) with myoclonus: report of two cases. Issue 6 (1st December 2001) - Carelli, V; Valentino, M L; Liguori, R; Meletti, S; Vetrugno, R; Provini, F; Mancardi, G L; Bandini, F; Baruzzi, A; Montagna, P
Abstract : The previously unrecognised association of myoclonus in two patients with LHON with the 11778/ND4 pathogenic mutation is described. EEG failed to disclose epileptic figures, and a back averaging study suggested that myoclonus was cortical in origin in both patients.